2013
DOI: 10.1002/eat.22169
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of rapid response to enhanced cognitive behavioral therapy in a routine clinic sample of eating disorder outpatients

Abstract: Early change in treatment is encouraged to achieve the best possible prognosis in CBT-E. Those who did not achieve rapid response still had an overall significant improvement in symptoms from pretreatment to post-treatment, but a lower rate of full remission. Nonrapid responders are an important group of patients to study because they offer researchers an opportunity to improve clinical decision-making and treatment outcomes for patients who are at risk of suboptimal response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
60
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 32 publications
7
60
2
Order By: Relevance
“…Additionally, given that failure to respond early to treatment may also be a risk factor for less favourable outcomes in the longer term, 46,47 identifying those individuals who fail to respond early in treatment could help to ensure that more intensive follow-up and intervention is conducted where appropriate.…”
Section: Implications For Treatmentmentioning
confidence: 98%
“…Additionally, given that failure to respond early to treatment may also be a risk factor for less favourable outcomes in the longer term, 46,47 identifying those individuals who fail to respond early in treatment could help to ensure that more intensive follow-up and intervention is conducted where appropriate.…”
Section: Implications For Treatmentmentioning
confidence: 98%
“…Conversely, one meta-analysis found that alliance was relevant to the outcome of therapy only when that therapy was relatively unstructured (i.e., nonbehavioral) (Crits-Christoph et al, 1991); though other meta-analyses have not replicated this distinction (Horvath et al, 2011). In EDs specifically, CBT researchers have questioned the relationship between alliance and outcome, with certain studies finding no relationship between alliance and outcome in CBT for anorexia nervosa (AN; e.g., Waller et al, 2012) and bulimia nervosa (BN; e.g., Raykos et al, 2013). …”
Section: Therapy Typementioning
confidence: 99%
“…A number of studies have observed strong associations between symptom change and therapeutic alliance in the first few weeks of treatment (Brown, Mountford, & Waller, 2013b;Constantino et al, 2005), as well as early symptom change and later outcomes (Le Grange, Accurso, Lock, Agras, & Bryson, 2014;Raykos, Watson, Fursland, Byrne, & Nathan, 2013). Thus, it could be argued that the alliance is simply a by-product of early symptom change, and that alliance-outcome associations that do not account for the role of early symptom change may be spurious (DeRubeis, Brotman, & Gibbons, 2005).…”
mentioning
confidence: 99%
“…Similarly, patients with BN who rapidly normalized their eating within the first four to six weeks of treatment had lower rates of binge eating and vomiting at post-treatment (Wilson, Fairburn, Agras, Walsh, & Kraemer, 2002). In transdiagnostic eating disorder samples, rapid reduction in the cognitive psychopathology of eating disorders (Raykos, Watson, Fursland, Byrne, & Nathan, 2013) and rapid normalization of eating (McFarlane, Olmsted, & Trottier, 2008) were associated with better remission rates and lower relapse rates, respectively. Despite the fact that rapid response to treatment has consistently been associated with higher remission and lower relapse rates, this literature is limited by the use of many different operational definitions of rapid response.…”
mentioning
confidence: 95%
“…Operational definitions of key constructs critically affect rates of relapse and affect interpretability and comparability of findings (Olmsted, Kaplan, & Rockert, 2005). Research on rapid response has defined the "initial period" of treatment as the first week (Zunker et al, 2010), first three weeks (McFarlane et al, 2008;Vaz et al, 2014), first four weeks (Agras et al, 2000;Fairburn et al, 2004;Grilo et al, 2006;McFarlane, MacDonald, Royal, & Olmsted, 2013;Olmsted et al, 1996, in press;Wilson et al, 2002;Zunker et al, 2010), first five weeks (Raykos et al, 2013), and first six weeks (le Grange et al, 2008;Wilson et al, 2002). The operationalization of response itself has also varied widely to include binge eating and/or vomiting reduction ranging from 49% to 85% within the first four to six weeks (i.e., Agras et al, 2000;Fairburn et al, 2004;Grilo et al, 2006;le Grange et al, 2008;Zunker et al, 2010).…”
mentioning
confidence: 97%